Quasispecies Changes with Distinctive Point Mutations in the Hepatitis C Virus Internal Ribosome Entry Site (IRES) Derived from PBMCs and Plasma - Luca Mercuri; Emma C. Thomson; Joseph Hughes; Peter Karayiannis (Advances in Virology)
The 5’ untranslated region (UTR) of the hepatitis C virus (HCV) genome contains the internal ribosome entry site (IRES), a highly conserved RNA structure essential for cap-independent translation of the viral polyprotein. HCV, apart from the liver, is thought to be associated with lymphocyte subpopulations of peripheral blood mononuclear cells (PBMCs), in lymph nodes and brain tissue. In this study, RT-PCR, cloning, and sequence analysis were employed to investigate the quasispecies nature of the 5’UTR following extraction of viral RNA from PBMCs and plasma of HCV infected individuals. The nucleotide variation between IRES-derived sequences from PBMCs and plasma indicated the existence of polymorphic sites within the IRES. HCV isolates had divergent variants with unique mutations particularly at positions 107, 204, and 243 of the IRES. Most of the PBMC-derived sequences contained an A-A-A variant at these positions. The mutations associated with the IRESes suggested the presence of unique quasispecies populations in PBMCs compared with plasma.